Supporting family carers in home-based end of life care: using participatory action research to develop a training programme for support workers and volunteers - Caswell, Glenys; Hardy, B.; Ewing, G.; Kennedy, S.; Seymour, Jane (BMJ Publishing Group, 2017)
Background: Family carers are crucial in enabling dying people to stay at home, but are often not prepared for their caring role, receiving little support from formal health and social care services. It is increasingly likely that any help or support family carers receive will be provided by a third sector organisation on either a voluntary basis or by untrained carer support workers. Objectives: To produce a training programme designed to equip carer support workers and volunteers with the basic skills and knowledge needed to support family carers. Process of development Participatory action research, a collaborative form of working in which those who are affected by an issue take a lead role in the research, was used. Bereaved carers acting as research partners, support workers and representatives of third sector organisations took an active part in designing, developing, piloting and refining the programme in a number of interlinked stages. During development the programme was piloted on four occasions and evaluated by 36 trainees and three trainers. Final training programme: The outcome of the project is an innovative, one day training programme, offering an introduction to supporting family carers who are looking after someone approaching the end of life. The use of participatory action research methods enabled the development of a programme that addresses support needs identified by bereaved carers and training needs identified by carer support workers. The finished programme includes all the materials necessary to run a training day for support workers and volunteers: facilitator’s notes, trainee workbook, slides, promotional poster and pre-course reading for trainees. Knowledge of issues involved in end of life and palliative care is not required, although some experience in delivering training is advisable. Conclusion: The programme evaluated well during development, but further research is required to examine the transfer of learning into the workplace.